PENERAPAN PENDEKATAN KONSTEKTUAL PADA MATA PELAJARAN PENGETAHUAN SOSIAL DI SEKOLAH DASAR - Arini Estiastuti (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2010)
The learning process that still traditional and focused to the given information from knowledge to the, student to trasnfer the knowledge as much as possible until the student as the mini library, so the learning become uninteresting and less meaningful, and do not develop creativity through the learning of social knowledge, they get knowledge, skill, and attitude and sense to face life. In order to the learning social knowledge become meaningful, the learning through the application of vicinity contextual that help the theacher to relate the material that thought with the situation in the student world realism and to encourage the student to make tine relation between knowledge that have to the application in their daily life. According to the result of research is advised to the teacher of fourth class elementary school that apply the contextual approach to the subject of social knowledge in order that the student can develop the knowledge and the skill basis that useful to themselves in the daily life.